Catalytic reduction of nitrate in water: Promoted palladium catalysts supported in resin - Neyertz, Claudia A. (2010)
The reactive properties of Pd–Cu and Pd–In catalysts over weak anionic exchange resin as support was investigated in the catalytic nitrate reduction. Pd–Cu/resin catalysts were prepared upon different copper fixation procedures (ion exchange method and controlled surface reaction). The samples were tested in a batch reactor with H2 bubbling and constant pH. The fresh and reacted catalysts were characterized by TEM, EPMA, XRD and XPS. The results demonstrated a higher activity of the Pd–Cu/resin catalyst prepared upon controlled surface reaction due to a high concentration of binary sites in the external surface. On the other hand, the XRD and TEM analyses indicated that sinterization occurs during reaction, leading to an increase in the average particle size. In the same way, a Pd–In/resin was investigated showing more activity and less selectivity than the Pd–Cu/resin sample.